(untitled) (Scientific journal of the Fergana State University, 2025)
The military and diplomatic interactions between Genghis Khan and the Jin Dynasty are pivotal in the geopolitical history of East and Central Asia. This article examines Genghis Khan’s campaigns against the Jin Dynasty, diplomatic negotiations, and the use of envoys as a critical political strategy. Drawing on the works of Rashid al-Din, H. Desmond Martin, Paul Ratchnevsky, and ancient Chinese chronicles like Yuanshi, the study explores the internal weaknesses of the Jin Dynasty and Genghis Khan’s military-diplomatic successes. The research highlights the historical significance of these relations and their impact on regional dynamics.